Effective administrative leadership in the implementation of public policies: Analytical look at the Baghdad Provincial Council - حسين فرح ضياء; جاسم همام فلاح (Journal of Economics and Administrative Sciences, 2017)
Abstract The current research aims to find out the role of administrative leadership in the implementation of public policies and their effectiveness and their ability to do so, As well as analysis and testing of influence and correlations between research variables, The researcher has the descriptive and analytical approach, And several tools used to gather information consisted of personal interviews and field visits, While distributed questionnaire tool that consists of (35) items on a sample consisting of (147) individuals formed of staff of the Baghdad Provincial Council. The research was based on a set of assumptions prove the level of influence and the strength of the link to the dimensions of the effectiveness of administrative leaders in the dimensions of the implementation of public policies, The answers were the sample using statistical analysis software (SPSS), The researcher used a number of statistical tools to extract the results, namely, (arithmetic mean, standard deviation, F test, the coefficient of determination R2, simple correlation coefficient, simple linear regression coefficient, coefficient of variation, percentage). The current research and reach to a number of key conclusions and most important: 1-The Baghdad provincial council has no clear vision in the way the wording of the structure of its work or enough to build plans, long-term policies, which identifies through the obvious weakness in the performance and motivation of employees in the Council, and also by not hold them responsibility or involve them in important decisions. 2- Statistical results showed that there was a link and effect relationship significant moral independent variable effective administrative leadership for its removal (blurred vision, empowerment, delegation, motivation, leadership style) variable -based implementation of public policies for its removal (drafting and publishing, planning and resource mobilization, stakeholders).